Real-world KINDLE-Latin America subset data on treatment patterns and clinical outcomes in patients with stage III non-small-cell lung cancer - Martin, CM (2023)
Introduction: Stage III non-small-cell lung cancer (NSCLC) management is challenging given the heterogeneous nature of the disease. The LATAM subset of the real-world, global KINDLE study reported the treatment patterns and clinical outcomes for LATAM from the pre-immuno-oncology era. Methods: The study was conducted in seven countries (Argentina, Chile, Colombia, Dominican Republic, Mexico, Peru and Uruguay) in stage III NSCLC (American Joint Committee on Cancer, 7th edition) diagnosed between January 2013 and December 2017. Retrospective data from patients' medical records (index date to the end of follow-up) were collected. Summary statistics, Kaplan–Meier survival estimates and a two-sided 95% confidence interval (CI) were provided. Cox proportional hazard model was used for univariate and multi-variate analyses. Results: A total of 231 patients was enrolled, the median age was 65.0 years (range 21.0–89.0), 60.6% were males, 76.6% had smoking history, 64.0% had adenocarcinoma and 28.7% underwent curative resection. Multiple treatment regimens (>25) were used; chemotherapy alone was the most common (24.8%). The overall median progression-free survival (mPFS) and median overall survival (mOS) were 14.8 months (95% CI, 12.1–18.6) and 48.6 months (95% CI, 34.7 to not calculable). Significantly better mPFS and mOS were observed for stage IIIA with curative surgery and resectable tumours and stage IIIB with an Eastern Cooperative Oncology Group score of 0/1, female gender, resectable tumours, adenocarcinoma and curative surgery (p < 0.05). Conclusion: Results show diversity in treatment practices and the corresponding clinical outcomes in stage III NSCLC. There is a need to streamline treatment selection and sequencing to decrease relapse rates after initial therapy.